2020
DOI: 10.1002/fsn3.1935
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and antidiabetic activity of essential oils encapsulated in gelatin‐pectin particles against sugar, lipid and protein oxidation and amylase and glucosidase activity

Abstract: Diabetes mellitus is mainly characterized by hyperglycemia, hyperlipidemia, and oxidative stress at sugar, lipid, and protein levels. Hyperglycemia can promote superoxide buildup through different metabolic pathways for instance; augmented glucose flux through the polyol pathway; increased protein glycation; protein kinase activation; hexosamine activation and decline in antioxidant defense

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In support of the findings of the study linear regression coefficients were calculated. Regression coefficient values near to 1 were observed for almost all the three biological activities performed indicating that these oil have antioxidant, anticholinesterase, and antidiabetic activities which is also obvious from the reported studies [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 65%
“…In support of the findings of the study linear regression coefficients were calculated. Regression coefficient values near to 1 were observed for almost all the three biological activities performed indicating that these oil have antioxidant, anticholinesterase, and antidiabetic activities which is also obvious from the reported studies [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 65%
“…The results show that carvacrol and p -cymene had a similar activity against α-amylase, with an IC50 of 171.1 and 215.2 μg/mL, respectively. Recently, Siahbalaei and coworkers [ 42 ] reported that some essential oils, rich in carvacrol, displayed vigorous antioxidant activity against glucose oxidation and anti-diabetic effects against amylase and glucosidase activities, suggesting their possible anti-diabetic potential. By molecular docking analysis, Pathak and coworkers [ 43 ] demonstrated that carvacrol had a good docking score toward the α-amylase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…One of the solutions for increasing the EOS stability might be their incorporation into the biopolymeric matrix. Siahbalaei et al [ 40 ] proposed the gelatin–pectin composite as a matrix for functional materials, which could be applied for food and cosmetic products and as a carrier for EOs in biomedical applications. Due to the antibacterial properties of thyme oil, Kamrudi et al [ 41 ] proposed nanocarriers based on polyamidoamine dendritic polymer (PAMAM).…”
Section: Resultsmentioning
confidence: 99%